The Victory of Jair Bolsonaro According to the Brazilian Electoral Study of 2018 - Amaral,Oswaldo E. do (2020)
The 2018 elections surprised most analysts and political scientists in Brazil and abroad. The competitive dynamic that opposed the PT and the PSDB in presidential elections since 1994 has been disrupted, resulting in a novelty for the Brazilian party system. The purpose of this research article is to identify the determinants of votes for Jair Bolsonaro in the two rounds of the 2018 presidential election from data collected by the Brazilian Electoral Study. By means of multivariate analyses of the two rounds of the presidential election, we found that flourishing 'antipetismo' (i.e. anti-Workers' Party sentiment), growing numbers of voters self-identifying as right wing and increased importance of variables linked to voters' political identification all underpinned the victory of Jair Bolsonaro.